The impact of social media usage intensity on self-esteem: survey on emerging adulthood of instagram user - Rahma, Lili Mira Julia; Setiasih, Setiasih (Universitas Islam Negeri Raden Intan Lampung, 2021)
Social media can be used to increase individual popularity, one of which is Instagram. Instagram can be used to increase individual self-popularity or increase self-esteem. The purpose of this study, namely to determine the relationship between the intensity of using Instagram and self-esteem in emerging adulthood. This research is a quantitative-survey research, with 259 students at “X” University as many as male and female participants aged 18-25 years. The measuring instrument used is the Rosenberg Self Esteem Scale and the Instagram Intensity Scale. The analysis used was the Spearman non-parametric correlation test. The results show that there is a significant correlation between the intensity of using Instagram and self-esteem on emerging adulthood, there is also a correlation between emotional attachment to Instagram and self-esteem on emerging adulthood. Thus the higher the intensity of using Instagram or the higher the emotional attachment to Instagram, the higher the self-esteem of emerging adulthood. The higher the intensity of a person using Instagram, the higher the desire or motivation of the individual to become more prominent.